Correlation analysis of serum SERPINA3, CLEC2 and hs-CRP/ALB with major adverse cardiovascular events (MACE) after percutaneous coronary intervention (PCI) in STEMI: Serum SERPINA3, CLEC2 and hs-CRP/ALB with MACE after PCI in STEMI - Ma, Yuncong; Fang, Suxia; Liu, Shasha; Jiang, Zhencong (Journal of Medical Biochemistry, 2025)
Objective To examine the main adverse cardiovascular events that occur in individuals who have had an acute ST-segment elevation myocardial infarction (STEMI) after receiving percutaneous coronary intervention (PCI), such as serum C-type lectin domain family member 2 (CLEC2), serine protease inhibitor family member A3 (SERPINA3), and high-sensitivity C-reactive protein/albumin (hs-CRP/ALB) levels.Methods The STEMI group included 132 patients who were observed for a year after being hospitalized to the hospital between January 2023 and September 2024.   The patients were divided into two groups: the MACE group and the non-MACE group, based on whether MACE came after PCI. Additionally, The control group consisted of 68 healthy people who were examined physically at the hospital throughout the same time period. Using an enzyme-linked immunosorbent test, the levels of serum CLEC2, SERPINA3, hs-CRP, and ALB were measured in each research participant, and the hs-CRP to ALB ratio was computed. After PCI, multivariate logistic regression was utilized to examine the variables affecting MACEs in STEMI patients. Receiver operating characteristic (ROC) curves were used to analyze the predictive value of single and combined detection of serum CLEC2, SERPINA3, and hs-CRP/ALB for MACEs in STEMI patients after PCI.Results The incidence of MACE after PCI in 132 STEMI patients was 31.06% (41/132). The levels of serum CLEC2, SERPINA3 and hs-CRP/ALB in the STEMI group were significantly greater than those in the control group (P
Keywords: Acute ST-segment elevation myocardial infarction; Percutaneous coronary intervention; Members of the C-type lectin domain family 2; Serine protease inhibitor family member A 3; Hypersensitive C-reactive protein/albumin